MRI Sagittal Image Segmentation from Patients with Abdominal Aortic Aneurysms - Desti Riminarsih; Cut Maisyarah Karyati; Achmad Benny Mutiara; Bambang Wahyudi; E. Ernastuti (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Early detection in patients with abdominal aortic aneurysm (AAA) is esdential to reduce the risk of rupture of aortic wall that causes bleeding and often lead to death. Information about the condition of AAA is indispendable to complete the diagnosis of doctors in decision making. The position and shape of AAA can be obtained by sagittal image from an MRI examination. Characteristics of MRI sagittal image are having a gray level that is almost teh same between one organ to another. Therefore, to separate between one organ to another is difficult. This research is conducted MRI sagittal iamge segmentation in patients to obtain information on morphology and location of abdominal aortic aneurysm (AAA). To Segmenting the MRI Image we comobine thresholding method and Haralick Method. Under this proposed method, obtained sagittal images of the aorta are used to gain information about the location and shape of the aneurysm in abdominal aorta.